2022
DOI: 10.1001/jamapediatrics.2021.5103
|View full text |Cite
|
Sign up to set email alerts
|

Social Risk Interventions and Health Care Utilization for Pediatric Asthma

Abstract: IMPORTANCE Social determinants of health (SDOH) correlate with pediatric asthma morbidity, yet whether interventions addressing social risks are associated with asthma outcomes among children is unclear.OBJECTIVE To catalog asthma interventions by the social risks they address and synthesize their associations with asthma-related emergency department (ED) visits and hospitalizations among children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 58 publications
2
13
0
Order By: Relevance
“…These creative interventions allow for both comprehensive and individualized solutions for patients and their families. A comprehensive systemic review and meta-analysis showed interventions that tackle social risk in children with asthma can decrease emergency room visits and hospitalizations, further supporting the work we do to decrease asthma disparities secondary to SDoH [110 ▪▪ ]. Although these interventions and assistance described in this review continue to be helpful, most are merely proxies for a larger systems issue that need to be addressed at a state and federal level.…”
Section: Targeted Interventions To Meet These Communities Most At Risksupporting
confidence: 55%
“…These creative interventions allow for both comprehensive and individualized solutions for patients and their families. A comprehensive systemic review and meta-analysis showed interventions that tackle social risk in children with asthma can decrease emergency room visits and hospitalizations, further supporting the work we do to decrease asthma disparities secondary to SDoH [110 ▪▪ ]. Although these interventions and assistance described in this review continue to be helpful, most are merely proxies for a larger systems issue that need to be addressed at a state and federal level.…”
Section: Targeted Interventions To Meet These Communities Most At Risksupporting
confidence: 55%
“…The objective of their study was to systematically review the association of social risk interventions with the utilization of health care for pediatric asthma by using the social determinants of health framework put forward by Healthy People 2020. 6 The Healthy People framework groups midstream interventions in 5 domains (ie, health, environment, community, education, and economic). 1 Tyris et al 6 found that when using this classification of asthma-oriented interventions, health, environment, and community interventions, especially in combination, were associated with reduced risk of health care utilization.…”
Section: Social Determinants Of Healthmentioning
confidence: 99%
“…6 The Healthy People framework groups midstream interventions in 5 domains (ie, health, environment, community, education, and economic). 1 Tyris et al 6 found that when using this classification of asthma-oriented interventions, health, environment, and community interventions, especially in combination, were associated with reduced risk of health care utilization. There was insufficient evidence for associations with economic or education interventions.…”
Section: Social Determinants Of Healthmentioning
confidence: 99%
“…Patients with SCD often have other chronic health conditions and comorbidities that can benefit from coordination of their health care services 13,[19][20][21][22][23] . Asthma can especially exacerbate sickle cell disease complications 21 , and asthma care is well-known to benefit from community health workers interventions (CHW) 24 . Other investigators have categorized acute ED and hospitalizations in SCD as unavoidable and avoidable.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to cold or wind increases the number of acute pain episodes that require hospitalization 25,26 . CHW can also assist with access to community resources, especially mental health services that could modulate SCD health care utilization 24,27,28 .…”
Section: Introductionmentioning
confidence: 99%